2012
DOI: 10.1530/joe-12-0255
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical suppression of GH-dependent isoforms of cytochrome P450 by the somatostatin analog octreotide

Abstract: Octreotide is a potent somatostatin analog therapeutically used to treat several conditions including hyper growth hormone secretion in patients with acromegaly. We infused, over 30 sec, octreotide into male rats every 12 h for 6 days at levels considerably greater than typical human therapeutic doses. Unexpectedly, resulting circulating growth hormone profile were characterized by pulses of higher amplitudes, longer durations and greater total content than normal, but still contained an otherwise male-like ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Plasma GH concentrations were determined by a sensitive sandwich ELISA method as described previously (Das et al, 2013a). Procedures for collecting unstressed postnatal plasma as well as adult serial blood sampling for GH determinations have been reported (Pampori et al, 1991a; Banerjee at al., 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma GH concentrations were determined by a sensitive sandwich ELISA method as described previously (Das et al, 2013a). Procedures for collecting unstressed postnatal plasma as well as adult serial blood sampling for GH determinations have been reported (Pampori et al, 1991a; Banerjee at al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, we previously reported that adult male rats and men cannot be induced (regardless of GH treatment) to express the normal female profile of hepatic CYPs (Dhir et al, 2006; Pampori and Shapiro, 1999; Thangavel et al, 2004; Thangavel and Shapiro, 2008; Thangavel et al, 2011) nor can adult female rats or women be induced to fully express the masculine CYP profile (Dhir et al, 2006; Thangavel et al, 2006; Thangavel and Shapiro, 2007; Dhir et al, 2007). The response of each of the dozen or so sex-dependent rat CYP isoforms to GH regulation has been described (Thangavel and Shapiro, 2008; Banerjee et al, 2014; Das et al, 2013a). If CYP enzymes were not imprinted, then irrespective of sex, the same adult treatment should produce the same CYP expression levels in males and females.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, trunk blood was collected from individual pups, in the morning from 09:00 to 10:00, representing all litters, at 2, 5, 8 and 11 days of age from both MSG- and vehicle-treated male rats. Circulating plasma GH profiles were determined by a sensitive sandwich ELISA method according to Steyn et al (2011) with modifications by us (Das et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Repetitive blood samples (40 μl) were obtained at 15‐min intervals from unrestrained, unstressed, and completely conscious hypox, neonatally MSG‐treated, and NaCl‐treated adult rats outfitted with our mobile catheterization apparatus (40) for 8 continuous hours. Circulating plasma GH profiles were determined by a sensitive sandwich ELISA method according to Steyn et al (41) with modifications by us (42).…”
Section: Methodsmentioning
confidence: 99%